Mini Review: the non-neuronal cardiac cholinergic system in type-2 diabetes mellitus - Saw, Eng Leng; Fronius, Martin; Katare, Rajesh; Kakinuma, Yoshihiko (Frontiers in Cardiovascular Medicine, 2024)
Diabetic heart disease remains the leading cause of death in individuals with type-2 diabetes mellitus (T2DM). Both insulin resistance and metabolic derangement, hallmark features of T2DM, develop early and progressively impair cardiovascular function. These factors result in altered cardiac metabolism and energetics, as well as coronary vascular dysfunction, among other consequences. Therefore, gaining a deeper understanding of the mechanisms underlying the pathophysiology of diabetic heart disease is crucial for developing novel therapies for T2DM-associated cardiovascular disease. Cardiomyocytes are equipped with the cholinergic machinery, known as the non-neuronal cardiac cholinergic system (NNCCS), for synthesizing and secreting acetylcholine (ACh) as well as possessing muscarinic ACh receptor for ACh binding and initiating signaling cascade. ACh from cardiomyocytes regulates glucose metabolism and energetics, endothelial function, and among others, in an auto/paracrine manner. Presently, there is only one preclinical animal model – diabetic db/db mice with cardiac-specific overexpression of choline transferase (Chat) gene - to study the effect of activated NNCCS in the diabetic heart. In this mini-review, we discuss the physiological role of NNCCS, the connection between NNCCS activation and cardiovascular function in T2DM and summarize the current knowledge of S-Nitroso-NPivaloyl-D-Penicillamine (SNPiP), a novel inducer of NNCCS, as a potential therapeutic strategy to modulate NNCCS activity for diabetic heart disease.